Inflammation and immunity in depression basic science and clinical applications - Baune, Bernhard T. (Academic Press, 2018)
Inflammation and Immunity in Depression: Basic Science and Clinical Applications is the first book to move beyond the established theory of cytokine-induced depression and explore the broader role the immune system plays in this devastating mood disorder. The book fully explores the most recent lines of research into this rapidly advancing field, including alterations of T-cells, the neurobiological implications of neuroinflammation and immune alterations for brain development and function, and the genetic components of neuroinflammation in depression, including the relationships between stress and inflammation that are revealing gene-environment interactions in the disorder. Combining contributions from researchers worldwide, this book provides the most comprehensive discussion available today on the involvement of the innate immune and adaptive immune systems in depressive disorder. Chapters span neuroscience, psychology, clinical applications and future directions, making this book an invaluable resource for advanced students, researchers and practitioners who need to understand the complex and varied role of inflammation and immune responses in depression.--Provided by publisher.